The study of soft factors in team selection for construction project - Liew, Pei Shan (2015)
Construction industry is important in developing a country towards a developed country. Meanwhile, the failure rate of construction project is increasing every year which cause the construction project become critical. There are many factors that caused the construction project failure which included poor planning, poor communication, natural disaster, selected the wrong team members and etc. This research will be conduct to find out about how soft factors affecting the team selection for construction project. The existing of soft factors in team selection is not be aware of construction industry. The list of soft factors is identified and to be verify in order to prove the existing of soft factors in team selection is used by the project manager unconsciously. The respondents of this research are the project manager or top management from construction project in Kuala Lumpur area. The result show that the soft factors is implemented by the project manager unconsciously. The most applied soft factors in team selection for construction project by the project manager is the team member’s competencies and characteristics. Therefore, the result is significant in finding the soft factors as a new factors that affecting the team selection.